Inquiry Strategy to Improve Student Learning Outcomes in Fiqh Learning at B MI Negeri 9 Aceh Tamiang - Mukhlis; Erwin Saiful Mizan (Journal of Action Research in Islamic Education, 2025)
The purpose of this study is to improve learning outcomes, creativity, critical thinking and student activity in the learning process on the material of Jama' and Qashar prayers in class III.B MIN 9 Aceh Tamiang in the 2022/2023 Academic Year. The method used in this classroom action research is the discussion method with an inquiry strategy as its facility. The subjects of this study were students of class III.B at MIN 9 Aceh Tamiang. The number of students is 26 students with 16 male students and 10 female students. This Classroom Action Research was carried out within 2 months, namely from September to October in the odd semester. The methodology of this research is classroom action research consisting of two cycles and each cycle consists of one meeting. Each cycle consists of planning, implementation, observation, and reflection. The research procedure consists of pre-research, cycle one planning, implementation of cycle one action, observation of cycle one, reflection of cycle one, planning of cycle two, implementation of cycle two action, observation of cycle two, and reflection of cycle two. Data collection techniques include collecting test scores carried out at the end of each learning cycle using a question instrument (written test). Observation data is carried out by looking at student activity in the learning process. Data are analyzed using percentage statistics. The results of the study showed that there was an increase in student learning completeness from 31.3% in the pre-study to 54.2% in cycle I and with an increase to 73.3%, completeness to 84.6% in cycle II. Learning activities increased from good to very good categories. The application of inquiry strategies can improve Fiqh learning activities and outcomes in the Jama' and Qashar Prayer materials in class III.B MIN 9 Aceh Tamiang, 2022/2023 Academic Year.